Reliability and validity of the Sinhala version of the PedsQL™ 3.0 Asthma Module in early adolescents with asthma in a district of Sri Lanka - MN Danansuriya; LC Rajapaksa; JW Varni (College of Community Physicians of Sri Lanka, 2011)
Objective: To examine the psychometric properties of the Sinhala version of the Pediatric Quality of Life Inventory™ (PedsQL™) 3.0 Asthma Module among adolescents with asthma in Sri Lanka. Methods: The PedsQL™ 3.0 Asthma Module patient self-report and parent proxy-report were translated into Sinhala and conceptually validated. A cross-sectional study was conducted among 140 adolescents (12-15 years), with physician diagnosed asthma and their caregivers (n=140). Reliability was assessed with Cronbach‟s alpha. Validity was evaluated by examining scale structure, by exploring interscale correlations and comparing across known groups. Results: PedsQL™ Asthma Module - Sinhala version was acceptable with minimal missing responses. All scales showed satisfactory reliability with 0.87 for the total scale scores for both patient and parent reports. Overall results of the multitrait scaling analysis confirmed the scale structure. Construct validity was confirmed by the inter-scale correlations between the domains for teen self-report and between teen and parent reports. The PedsQL™ Asthma Module showed convergent validity with PedsQL™ 4.0 Generic Core Scales and was able to discriminate adolescents with controlled and uncontrolled asthma Conclusion: The PedsQL™ 3.0 Asthma Module- Sinhala version is a reliable and valid instrument to measure asthma-specific health related quality of life among adolescents with asthma in Sri Lanka. Key words: PedsQL™; Asthma; Sri Lanka; Adolescents; Health related quality of life DOI: http://dx.doi.org/10.4038/jccpsl.v16i1.3866   Journal of the College of Community Physicians of Sri Lanka Vol.16(1) 2011, p.8-16